MANAJEMEN PENGASUHAN DALAM PEMBENTUKAN KARAKTER PANCA JIWA DI PONDOK PESANTREN AL BASYARIYAH CIGONDEWAH - Sanjaya, Dinar; Hasan J, Muhamad; Suwandari, Lilis; Teti Ratnawulan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT Islamic boarding schools (pesantren) represent Islamic educational institutions that possess a distinctive nurturing system in shaping students’ character in a holistic and sustainable manner. One of the fundamental values that forms the core of pesantren education is the Panca Jiwa, which consists of sincerity, simplicity, self-reliance, Islamic brotherhood, and fighting spirit. Amid the challenges of globalization, digitalization, and increasing moral complexity among younger generations, a well-structured and continuous nurturing management system is required to ensure that these values are effectively internalized in students’ daily lives. This study aims to analyze nurturing management in the formation of Panca Jiwa character at Al-Basyariyah Islamic Boarding School, Cigondewah, focusing on the aspects of planning, implementation, evaluation, and follow-up within the student nurturing process. This research employs a qualitative approach using a case study method. Data were collected through participatory observation, in-depth interviews with pesantren leaders, the director of student nurturing, teachers, and student administrators, as well as documentation analysis. The findings indicate that nurturing management at Al-Basyariyah Islamic Boarding School is implemented systematically and is deeply rooted in pesantren culture, involving all elements of the boarding school community. The internalization of Panca Jiwa values is realized through religious habituation, daily discipline, student independence, literacy programs, and the exemplary conduct of caregivers. Evaluation is conducted through both formal and informal mechanisms and is reinforced by the practice of muhasabah as a form of spiritual reflection. This study concludes that nurturing management integrated with pesantren culture is effective in shaping students’ Panca Jiwa character and has strong potential to serve as a contextual and sustainable model of community-based character education. Keywords: nurturing management, Panca Jiwa character, character education, Islamic boarding school, students